Tata kelola perusahaan dan manajemen laba terhadap kebijakan dividen di Indonesia - Budi Chandra; Novia Junita (Jurnal Ekonomi Modernisasi, 2021)
This research expected to understand the effect of corporate governance and earning management on dividend policy. The dependent variable selected for the research was the dividend payout ratio, while the independent variable was determined by the size of the board of commissioners, independence of board commissioners, managerial ownership, individual ownership, institutional ownership, directional accrual, firm age, firm size, leverage, and profitability. Samples for research were all companies registered under the Indonesia Stock Exchange, these were chosen using a purposive sampling method with a total of 865 observational data that met the criteria for 5 years. The panel regression method is used to analyze the impact of each independent variable on the dependent variable. The fixed-effects model is found to be the best regression model in this research. The research concludes that individual ownership, institutional ownership and profitability have a significant positive effect on dividend policy. Meanwhile, the size of the board of commissioners, independence of board commissioners, managerial ownership, earning management, firm size, firm age and leverage do not affect dividend policy. Real earning management and ownership factors are encouraged in future studies such as family ownership, public ownership, and foreign ownership in examining the impact on dividend policy.